ANALISIS PERSEPSI PENUMPANG TERHADAP PELAYANAN DAN WAKTU PERJALANAN “TEMAN BUS” TRANS MAMMINASATA DI KOTA MAKASSAR (STUDI KASUS KORIDOR II: MAL PANAKKUKANG-BANDARA SULTA HASANUDDIN) - Leatemia , Janoval; Mursalim; Kalangi, Hendry Tanoto (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Atma Jaya Makassar, 2024)
Public transportation that is orderly, economical, smooth, safe and comfortable is the choice made in developing an urban public transportation system. Buy the service is a service purchasing system by the government for public transport operators, TEMAN Bus (Transportation, Economical, Easy, Reliable and Comfortable) is the implementation of a service purchasing program or better known as buy the service (BTS) by the Ministry of Transportation of the Republic of Indonesia. This research aims to determine passenger perceptions of TEMAN Trans Mamminasata Bus service and travel times. This type of research uses descriptive research with a quantitative approach. To determine passenger perceptions using a scoring system developed from the Likert scale in data processing which is expressed in 6 variables for service level, namely safety, security, equality, affordability, comfort, regularity. Meanwhile, to determine travel time, use the direct measurement method by measuring the time from the point of departure to the point of destination. Based on the results of the research carried out, it was obtained that passenger perceptions of the TEMAN Bus Trans Mamminasata service received a score of 4.630 with a percentage of 92.601% (very good). The travel time for Panakkukang Mall-Sultan Hasanuddin Airport is 1 hour 15 minutes 32 seconds, Sultan Hasanuddin Airport-Panakkukang Mall is 1 hour 2 minutes 2 seconds and Panakkukang Mall- Sultan Hasanuddin Airport-Panakkukang Mall is 2 hours 17 minutes 34 seconds.